2000
DOI: 10.1039/b003437l
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modelling of surfactant monolayers under constraints derived from neutron reflectance measurements

Abstract: Reverse Monte Carlo simulations have been carried out to provide molecular-level detail on the structures of three different lipid and surfactant monolayers of particular relevance in the design and development of drugs and drug delivery systems. The simulations were performed using the SURFISS program, with the orientations and conformations of the molecules in the monolayers optimised iteratively using constraints furnished from neutron reflectance-derived volume fraction profile data. The three systems mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(4 reference statements)
1
5
0
Order By: Relevance
“…Surfactant behaviour has been modelled on the basis of neutron reflectivity data, including the roughness parameter of the fitted interfaces. 41 Bead models of modular proteins of the known 3-D structure have been used to define their overall spatial arrangement 42 in the interpretation of analytical ultracentrifugation data 43 and neutron data. 44 We are currently acquiring data for FIII9 0 10 molecules specifically oriented at gold surfaces through a C-terminal thiol and intend to develop bead models for these simplified protein layers before moving to the FIII9-10/integrin layers described here.…”
Section: Discussionmentioning
confidence: 99%
“…Surfactant behaviour has been modelled on the basis of neutron reflectivity data, including the roughness parameter of the fitted interfaces. 41 Bead models of modular proteins of the known 3-D structure have been used to define their overall spatial arrangement 42 in the interpretation of analytical ultracentrifugation data 43 and neutron data. 44 We are currently acquiring data for FIII9 0 10 molecules specifically oriented at gold surfaces through a C-terminal thiol and intend to develop bead models for these simplified protein layers before moving to the FIII9-10/integrin layers described here.…”
Section: Discussionmentioning
confidence: 99%
“…When scaled (as above), to relate to the E 12 chain dimensions, we thus find that the intrinsic lengths of the head groups vary between ∼8 Å (at 15 mN/m) and ∼20 Å (at 40 mN/m). Now, although it is possible to use these data to calculate the E 12 head group tilt-in a manner analogous to that used for the C 18 chains-as we have noted before [29], any such estimations of the E 12 tilt angles (unlike those made for the C 18 chains) are likely to be wholly misleading: molecular modelling studies of the 2C 18 E 12 monolayer structure (using the SURFISS program [30]) have shown that this monolayer has a highly heterogeneous mix of E 12 chain orientations and conformations (cf. Fig.…”
Section: Neutron Reflectometrymentioning
confidence: 98%
“…8). The SURFISS modelling gave evidence for a significant incidence of gauche links in the E 12 chains (averaging ∼16%), with some head groups being curled completely away from the water surface and having their methoxy termini buried deep amongst the C 18 chains [29]. It is apparent, therefore, that the head groups in the 2C 18 E 12 monolayer behave in a much more random coil manner, and so it is more informative to relate the calculated intrinsic E 12 chain dimensions to the root-mean-square end-to-end lengths ( R 2 1/2 ) expected for polyoxyethylene chains anchored to an impenetrable wall [31].…”
Section: Neutron Reflectometrymentioning
confidence: 98%
“…Zhan et al 21 performed MD simulations of hydroxylated alkylsilane SAMs on a planar silica substrate, showing that the molecular tilt angle is determined not only by coverage but also by the specific molecular arrangement of the silane molecules on the substrate. Barlow et al 22 observed that the bonded OTS layer on silica is essentially crystalline near the substrate, but more disordered and fluid-like far from it. Barriga et al 23 ran MD simulations of OTS SAMs on silica at different high coverage, molecular arrangement of the molecules bonded to the substrate, molecular orientation, and temperature.…”
Section: ■ Introductionmentioning
confidence: 99%